2020
DOI: 10.1093/nutrit/nuaa024
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the influences of food store product placement on dietary-related outcomes

Abstract: Context Product placement strategies have been used to influence customers’ food purchases in food stores for some time; however, assessment of the evidence that these techniques can limit unhealthy, and promote healthy, food choices has not been completed. Objective This systematic review aimed to determine how product placement strategies, availability, and positioning, in physical retail food stores located in high-income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 76 publications
(348 reference statements)
0
54
0
Order By: Relevance
“…Multiple studies have cited the importance of particular determinants, such as taste [ 51 , 52 ], healthiness/nutrition [ 53 ], time and convenience [ 54 ], gender [ 55 ], psychological or behavioural factors [ 54 ], societal influence [ 51 ], accessibility [ 6 ], packaging and labelling [ 56 , 57 ], advertising, marketing, and promotion [ 55 , 58 ], availability [ 6 , 54 , 59 ], and sociocultural acceptability [ 54 ]. Food store practices, including placement of healthy and unhealthy products, the amount of shelf-space allocated to these [ 60 ], and promotions and pricing policies, such as subsidising fresh foods [ 48 , 61 ] have been cited as important factors in consumer food choice too. Some scholars consider that the perception that a recommended diet costs more than current diets is a contributing factor to food choice, especially in low-income households [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have cited the importance of particular determinants, such as taste [ 51 , 52 ], healthiness/nutrition [ 53 ], time and convenience [ 54 ], gender [ 55 ], psychological or behavioural factors [ 54 ], societal influence [ 51 ], accessibility [ 6 ], packaging and labelling [ 56 , 57 ], advertising, marketing, and promotion [ 55 , 58 ], availability [ 6 , 54 , 59 ], and sociocultural acceptability [ 54 ]. Food store practices, including placement of healthy and unhealthy products, the amount of shelf-space allocated to these [ 60 ], and promotions and pricing policies, such as subsidising fresh foods [ 48 , 61 ] have been cited as important factors in consumer food choice too. Some scholars consider that the perception that a recommended diet costs more than current diets is a contributing factor to food choice, especially in low-income households [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prominent positioning of meat-free products had a significant long-lasting effect on sales of these products. Recent systematic reviews support the value of positioning strategies in retail environments to improve the nutritional quality of food purchases [13,14]. Evidence suggests that there is a greater likelihood of change when more options are available [24], and repeated exposure can also elicit increased acceptability or establish a new social norm about the presence of new products [25].…”
Section: Plos Medicinementioning
confidence: 99%
“…Systematic reviews that have drawn on broader evidence relating to interventions to shape food purchasing have found moderate-to low-quality evidence that product placement strategies (e.g., availability or prominent positioning (end of aisles, checkouts, or at eye level)) implemented in food retail environments can influence dietary behaviours [13,14]. Also, "crosscategory merchandising" (where complementary products are colocated in a store) is an established sales mechanism to increase sales [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…With Woolworths, Coles, and Metcash (IGA) combined representing 75% of the grocery market share in Australia [7], the high percentage of unhealthy food on price promotions at prominent displays likely reflects the lived experience for the majority of Australians when shopping in supermarkets. Research has found that, independently, price promotions and placement strategies can increase food and beverage purchases and consumption [15,43,44], and combined, placement strategies can exacerbate the promotional effect of price promotions [19]. It is therefore reasonable to assume that an environment that favours price promotions on unhealthy foods and beverages, especially when located in promotional areas, will result in increased sales of unhealthy products.…”
Section: Discussionmentioning
confidence: 99%